Tinjauan Yuridis terhadap Eksekusi Jaminan Fidusia dalam Kredit Bermasalah Ditinjau dari Undang-Undang Fidusia Nomor 42 Tahun 1999 - Stefanus Snak; Kelvin Eka Putra Banu; Stefanus Don Rade (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to (1) determine the legal provisions regarding the execution of fiduciary guarantees based on Law Number 42 of 1999 concerning Fiduciary Guarantees, (2) determine the legal limitations in the execution of fiduciary guarantees against problematic credit based on applicable legal provisions. The type of research used is normative legal research, using a qualitative approach. The results of the study indicate that although normatively fiduciary execution can be carried out directly by the creditor based on a fiduciary certificate that has executorial power, in practice various obstacles arise. These obstacles include the unregistered fiduciary deed, imperfect agreements, debtor approval, to the decision of the Constitutional Court which guarantees the existence of a default agreement and court involvement if an agreement occurs. This study concludes that legal protection for debtors is getting stronger, but the effectiveness of fiduciary as a credit guarantee faces new challenges in its implementation.